(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
We live in a progressive community, where economic, environmental, and socialconcerns surpass national and corporate boundaries. Organizations that act in a sustainable routine notonly help maintain the welfare of the globe and people, but they also generate businesses that willpersist and prosper in the long run.The relevance of the present study originates from a modest attempt to help focus attention on the needfor a better coordination of sustainability practices for managing the firm’s financial performance in oneof the fastest growing and the other, one of the most developed economies of the world. The studyattempts to scrutinize the influence of Sustainability Practices on Firm’s Financial Performance incontext of Canadian Corporate Sector using econometric tools.A literature review on empirical evidence of Relationship between Sustainability Practices and FinancialPerformance of select studies across the globe are presented in form of a summary of the study, author,year, country, sample size, time-period and technique adopted along with reported results.To investigate dynamics of the long-run relationship between, Corporate Sustainability Practices andFinancial Performance in Canadian corporate sector for the period 2007-2008 to 2019-2020, the Modelintends to employ Co integration and Granger Causality Test using an ARDL framework. This modeluses the annual data for variables – Return on Assets, Return on Capital Employed, Earnings per share,Economic, Environmental and Social Performance Indicators. The study perceives a linear associationamongst Sustainability Practices and Financial Performance for panel data for the period of 1997-98 to2019-2020 of 250 companies each listed on TSX. The resultant co integrating relationship betweenSustainability Practices and Financial Performance is consistent with the findings of other research inthe field.